IMPLEMENTING TAZKIYAH AL-NAFS IN THE DEVELOPMENT OF STUDENT CHARACTER - Ibrahim, Mulyadi; Rijal, Syamsul; Mawardi, Mawardi; Miswari, Miswari; Sihotang, Burhanuddin (State Islamic University North Sumatra, 2025)
Contemporary character education often lacks integration with spiritually rooted frameworks, particularly those grounded in Islamic traditions of inner purification. Despite the richness of concepts such as tazkiyah al-nafs, their practical application in modern educational settings remains limited. This study explores the concept of tazkiyah al-nafs as articulated by Abū Hasan Al-Nadwī and its relevance to contemporary character education. Using a descriptive-analytical approach, the research examines primary texts and scholarly interpretations to assess its pedagogical potential. The findings indicate that Al-Nadwī’s formulation—though distinct in its technical articulation—aligns with other scholars in four key aspects: its foundation in Qur’anic and Prophetic teachings, its position as an alternative to philosophical Sufism, its emphasis on ethical-spiritual purification through worship and social conduct, and its role in developing inner discipline. The study proposes a model for integrating tazkiyah al-nafs into character education through curriculum design, institutional culture, and a spiritually conscious learning environment.